Orange (Citrus sinensis) essential oil inclusion in high-energy diets for feedlot lambs: productivity, eating behavior, carcass characteristics, rumen morphometry, and fatty acid profile of the meat - Dias Junior, Paulo César G.; da Silva, Adrielly L.A.; dos Santos, Isabela J.; Soares, Leticia C.B.; Carlis, Matheus S.P.; Vicente, Ana Carolina S.; de Souza, Terezinha T.; de Assis, Rhaissa G.; Biava, Janaina S. [UNESP]; Quigley, Simon; Pires, Alexandre V.; Ferreira, Evandro M. (Elsevier, 2024)
This study evaluated the effect of different orange essential oil (OEO) inclusion rates on live weight gain, eating behavior, carcass characteristics, morphology of the ruminal epithelium, and fatty acid profile in the meat of feedlot lambs. Forty uncastrated Dorper × Santa Inês ram lambs with an initial average body weight of 21.8 ± 4.7 kg and average age of 86 ± 15 days were allocated to one of five dietary treatments in a randomized complete block design. Dietary treatments consisted of a 90:10 concentrate-to-forage ratio total mixed ration supplemented as follows: 1. non-additive supplementation (Control), and 2. additive supplementation with 100, 500, and 1000 mg OEO/kg diet DM (OEO100, OEO500, and OEO1000) or with 25 mg sodium monensin/kg diet DM (MON). The feeding lasted 84 d. Supplementation with OEO increased linearly dry matter intake (DMI), growth rate and feed efficiency (FE). Because of the linear increases in growth rate and the efficiency of energy utilization of the diet, lambs receiving OEO exhibited a greater (increasing linear effect) hot carcass weight (HCW), Longissimus muscle area (LMA), subcutaneous fat thickness (SFT), and body wall thickness (BWT) than lambs fed with Control. Lambs fed MON had lower DMI, growth rate and FE than Control and OEO. Compared to Control and OEO supplemented, lambs that received MON showed lower HCW, LMA, SFT, and BWT. Lambs fed with MON had lower oocyst counts than lambs fed with all other treatments. Lambs fed with MON spent more time eating and ruminating, with higher chewing rates than lambs fed all other diets. Rumen morphometry was unaffected by dietary treatment. The OEO supplementation increased the sum of monounsaturated fatty acids, improved the human health promotion index (HP index), and reduced the thrombogenicity index in the meat relative to lambs fed the MON treatment. Under the conditions in which the experiment was conducted, the inclusion of up to 1000 g/kg diet DM in high-energy finishing diets promotes DMI and improved growth performance and FE. Improvements in the carcass (HCW, LMA, and BTF) with OEO supplementation were mainly due to improvements in growth rate rather than effects on gain composition. Based on growth performance and carcass characteristics, OEO was a superior feed additive to sodium monensin. The OEO supplementation has a discreet effect on the fatty acid profile of the meat, but it is sufficient to improve the HP index. These findings highlight its potential as an effective additive for enhancing lamb productivity.
Keywords: Additive; Bio inputs; Citrus by-product; Limonene; Sheep; Sodium monensin